A microfluidic chip-based multivalent DNA walker amplification biosensor for the simultaneous detection of multiple food-borne pathogens. Issue 5 (27th January 2023) - Xu, Zhenli; Wang, Jiaqi; Jia, Zhijian; Wu, Yong-Xiang; Gan, Ning; Yu, Shaoning
Abstract : A multivalent DNA walker amplification biosensor combined with the microfluidic chip for simultaneously and sensitively detecting V.P, S.T, and S.A bacteria. Abstract : The rapid, simultaneous, sensitive detection of the targets has important application prospects for disease diagnosis and biomedical studies. However, in practical applications, the content of the targets is usually very low, and signal amplification strategies are often needed to improve the detection sensitivity. DNAzyme-driven DNA walkers are an excellent signal amplification strategy due to their outstanding specificity and sensitivity. Food-borne pathogens have always been a foremost threat to human health, and it is an urgent demand to develop a simple, rapid, sensitive, and portable detection method for food-borne pathogens. In addition, there are various species of pathogens, and it is difficult to simultaneously detect multiple pathogens by a single DNA walker. For this reason, a substrate strand with three rA cleavage sites was cleverly designed, and a multivalent DNA walker sensor combined with the microfluidic chip technology was proposed for the simultaneous, rapid, sensitive analysis of Vibrio parahaemolyticus, Salmonella typhimurium, and Staphylococcus aureus . The developed sensor could be used to detect pathogens simultaneously and efficiently with low detection limits and wide detection ranges. Moreover, the combination of gold stirring rod enrichment and DNA walker achieved double amplification, which greatly improved the detection sensitivity. More importantly, by changing the design of the substrate chain, the sensor was expected to be used to detect other targets, thus broadening the scope of practical applications. Therefore, the sensor can build novel detection tool platforms in the field of biosensing.